The Influence of Organizational values Toward Vision Achievement: case Study at SBM ITB - Tanzil, Belinda; Bangun, Yuni Ros (Journal of Business and Management, 2014)
A common response to globalization in most institutions is to become a world-class institution. SBM-ITB is one of the institutions that has a vision to be a world-class institution that inspires and develops new leaders with entrepreneurial spirit. One way to achive the vision is to conduct the values of an organization. This research aims to find out the influence of organizational values toward vision achievement in SBM-ITB. The models of organizational values and vision achievement are based on data from SBM-ITB’s website. The independent variable in this research is the organizational values, while the dependent variable is the vision achievement. The data retrieval is done by spreading the questionnaire and then processing it using the multiple linear regression analysis. The multiple linear regression analysis is used to find the relationship between the organizational values and the vision achievement. In data processing, the assumptions to fulfill the requirements of multiple linear regression is also tested. The findings of this research conclude that organizational values variable consisting of trust, excellence, harmony, integrity, and innovativeness simultaneously (together) and significantly influence on the vision achievement for academic, and non-academic employees. This is evidenced by the result of the F-test with significance probability below 0.05. The organizational value individually that has positive and significant influence toward the vision achievement are innovativeness and trust (for academic employees), harmony (for non-academic employees). This is evidenced by the result of the T-test with significance probability below 0.05.Keywords: organizational values, vision achievement, multiple linear regression